Muscle-Bone Crosstalk in the Masticatory System: From Biomechanical to Molecular Interactions - Buvinic, Sonja; Balanta-Melo, Julián; Kupczik, Kornelius; Vásquez, Walter; Beato, Carolina; Toro-Ibacache, Viviana (Frontiers in Endocrinology, 2021)
The masticatory system is a complex and highly organized group of structures, including craniofacial bones (maxillae and mandible), muscles, teeth, joints, and neurovascular elements. While the musculoskeletal structures of the head and neck are known to have a different embryonic origin, morphology, biomechanical demands, and biochemical characteristics than the trunk and limbs, their particular molecular basis and cell biology have been much less explored. In the last decade, the concept of muscle-bone crosstalk has emerged, comprising both the loads generated during muscle contraction and a biochemical component through soluble molecules. Bone cells embedded in the mineralized tissue respond to the biomechanical input by releasing molecular factors that impact the homeostasis of the attaching skeletal muscle. In the same way, muscle-derived factors act as soluble signals that modulate the remodeling process of the underlying bones. This concept of muscle-bone crosstalk at a molecular level is particularly interesting in the mandible, due to its tight anatomical relationship with one of the biggest and strongest masticatory muscles, the masseter. However, despite the close physical and physiological interaction of both tissues for proper functioning, this topic has been poorly addressed. Here we present one of the most detailed reviews of the literature to date regarding the biomechanical and biochemical interaction between muscles and bones of the masticatory system, both during development and in physiological or pathological remodeling processes. Evidence related to how masticatory function shapes the craniofacial bones is discussed, and a proposal presented that the masticatory muscles and craniofacial bones serve as secretory tissues. We furthermore discuss our current findings of myokines-release from masseter muscle in physiological conditions, during functional adaptation or pathology, and their putative role as bone-modulators in the craniofacial system. Finally, we address the physiological implications of the crosstalk between muscles and bones in the masticatory system, analyzing pathologies or clinical procedures in which the alteration of one of them affects the homeostasis of the other. Unveiling the mechanisms of muscle-bone crosstalk in the masticatory system opens broad possibilities for understanding and treating temporomandibular disorders, which severely impair the quality of life, with a high cost for diagnosis and management.